Legal Review of the Mechanism of Commission III of the House of Representatives of the Republic of Indonesia in Resolving Public Complaints : Tinjauan Yuridis Mekanisme Komisi III Dewan Perwakilan Rakyat Republik Indonesia dalam Rangka Menyelesaikan Pengaduan Masyarakat - Gea, Poppy Primadana Top; Rasji, Rasji (Indonesian Journal of Law and Economics Review, 2025)
General Background: Komisi III DPR RI holds a strategic supervisory role in Indonesia’s legal governance, particularly in ensuring accountability and justice within law-enforcement institutions. Specific Background: The increasing volume of public complaints indicates growing public reliance on legislative oversight to address perceived injustices, procedural irregularities, and allegations of abuse of authority in the criminal justice system. Knowledge Gap: Despite its significance, the mechanism for processing complaints in Komisi III lacks standardized procedures and remains underexplored in academic legal studies, especially regarding its conformity with constitutional principles and good governance. Aims: This study aims to analyze the legal basis, implementation, and limitations of Komisi III’s complaint-handling mechanism, as well as identify structural and normative barriers that affect its effectiveness. Results: The findings show that complaints are handled through stages of submission, verification, hearings, and recommendations, yet face obstacles such as unclear boundaries of authority, absence of SOPs, bureaucratic constraints, political intervention, and weak inter-institutional coordination. Novelty: This research provides a comprehensive normative-juridical assessment integrating legal doctrine with practical institutional dynamics. Implications: Strengthening procedural clarity, transparency, and technology-based administration is essential to enhance Komisi III’s constitutional role in ensuring accountable, responsive, and rights-oriented law enforcement in Indonesia. Highlights: Komisi III’s complaint mechanism lacks standardized SOPs, creating inconsistencies. Political dynamics and limited authority hinder effective follow-up of cases. Strengthening transparency and digital systems is essential to improve public trust. Keywords: Komisi III DPR RI, Public Complaints, Legislative Oversight, Legal Mechanism, Accountability